Agenda setting in social media election campaigns - Lehrner, Stefan (Eximia, 2022)
In modern democracies, elections play a very special role, as they are a guarantee of democratic participation by the electorate. For political parties, elections are the time to get in touch with their voters. With the proliferation of social media sites like Facebook and Twitter, Web 2.0 has become a reality and is increasingly used by parties. Using the example of the 2019 National Council election in Austria, this paper examines how parties use social media and which issues they specifically address in the election campaign on Facebook and Twitter. The following hypotheses are examined in this work: (1) Economic parties tend to focus on popular topics such as environmental protection, society or politicians in general news coverage on the social media sites Facebook and Twitter - compared to nationalist parties.(2) Environmental parties also focus on issues such as environmental protection on the social media sites Facebook and Twitter.(3) Negative campaigning plays a bigger role on Twitter than on Facebook.(4) The top candidates Sebastian Kurz and Pamela Rendi-Wagner also focus on the core topics of the parties (ÖVP = economy, SPÖ = welfare state) on the social media sites Facebook and Twitter.